EFL students’ emotional responses to oral feedback: The case of Indonesia - Purwandari, Junita Duwi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Feedback, a crucial component in supporting student learning, has been subject to extensive research in the field of English as a Foreign Language (EFL). Although some studies have explored students' emotional reactions to written feedback provided by teachers, there is a scarcity of research on emotional responses to oral feedback. Thus, this case study seeks to enhance the existing literature by investigating how students emotionally react to oral feedback. The study argues that the manner in which oral feedback is delivered can elicit unexpected emotional responses from students. This study was conducted in three senior high schools in Jakarta, Indonesia, with six participants from each school. Each student participated in a semi-structured interview, resulting in a total of 18 interview data. Thematic analysis was employed to analyze the data. The findings revealed that students expressed both positive and negative emotions in response to teacher oral feedback, with a tendency towards the latter outweighing the former, resembling an imbalanced scale. This study contributes to a deeper understanding of students' reactions to oral feedback and encourages teachers to reflect on their feedback practices.